Common law property theory and jurisprudence in Canada - Hamill, Sarah E. (Queen's Law Journal, 2015)
In recent years, property theorists have offered varying accounts as to what exactly ownership is, typically focusing on one or more key rights to the owned thing. However, most of these theories are articulated in the abstract and do not engage the jurisprudence. This article uses the jurisprudence concerning expropriation and adverse possession to show that Canadian courts have in fact developed their own definition of ownership-one that is not reflected in the property theory discourse. The author goes on to argue that this narrower definition of ownership-made up by the rights to exclude and to primary use-is preferable to those offered by the property theorists, as it better balances the competing interests of owners, non-owners and the state.